Peroxisomal ether lipid synthesis regulates cortical neurogenesis and maintains mitochondrial energy homeostasis in radial glial cells - Lin Li; Wenzheng Zou; Yuqing Lv; Yingfei Lu; Jiaqi Liang; Shukui Zhang; Baoyang Hu; Jianwei Jiao (Proceedings of the National Academy of Sciences, 2026)
Neurogenesis is characterized by dynamic structural changes and functional remodeling of multiple organelles, which interact to form an intricate network that precisely modulates processes including neural progenitor cell self-renewal, neurogenesis, and terminal neuronal development. However, the spatiotemporal dynamics of peroxisomes and their functional contributions within this regulatory network remain incompletely defined during mammalian cortical development. Here, we found that radial glial cells (RGCs) exhibit enriched peroxisome abundance, whereas neural differentiation is associated with reduced peroxisome numbers and increased pexophagy, accompanied by the remodeling of lipid metabolic programs. Acute disruption of peroxisomes by PLAAT3-PEX11 impaired neural differentiation in the embryonic mouse cortex, while PEX7 knockout compromised neurogenic progression in human cortical organoids, supporting a conserved requirement for peroxisomal function during cortical development. Lipidomic and imaging analyses revealed that peroxisome-derived ether lipids were essential for driving neural differentiation and were specifically enriched in mitochondria. Consistently, knockdown of Gnpat , which catalyzes the initial step of ether lipid biosynthesis, reduced neural differentiation, and disrupted mitochondrial structure and function, while batyl alcohol supplementation partially restored these defects. Mechanistically, the ether lipids maintain the structural integrity of mitochondrial cristae and thereby support respiratory chain activity, which in turn promotes oxidative phosphorylation and activates the NAD + associated signaling. Collectively, this work highlights the precise spatiotemporal regulation of neurogenesis through peroxisomal dynamics and interorganelle crosstalk and identifies ether lipids as a potential therapeutic target for neurodevelopmental disorders.